2005
DOI: 10.1080/00908310490448073
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Natural Oils in Seawater

Abstract: Spills of non-petroleum hydrocarbons including vegetable oils and fish oils are of environmental concern because of their potential to cause serious effects on marine life and coastal environments. Biodegradation by indigenous microorganisms is an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Many of these studies address the impact and management of hydrocarbon spills in Antarctica and other cold environments and provide valuable information on the indigenous and imported hydrocarbon‐degrading microorganisms. Other relevant studies examined the microbial content and environmental biodegradation of nonpetroleum hydrocarbons, including vegetable oils (Cornish et al ., ; Al‐Darbi et al., ; Dayrit et al ., ; Okechalu et al ., ; Tsiamis et al ., ). Our results, finding a substantial microbial content in the coconut oil‐based NEEM drilling fluid, corroborate other studies demonstrating the existence of large and diverse populations of microorganisms in hydrocarbon‐rich substances and contaminated environments.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies address the impact and management of hydrocarbon spills in Antarctica and other cold environments and provide valuable information on the indigenous and imported hydrocarbon‐degrading microorganisms. Other relevant studies examined the microbial content and environmental biodegradation of nonpetroleum hydrocarbons, including vegetable oils (Cornish et al ., ; Al‐Darbi et al., ; Dayrit et al ., ; Okechalu et al ., ; Tsiamis et al ., ). Our results, finding a substantial microbial content in the coconut oil‐based NEEM drilling fluid, corroborate other studies demonstrating the existence of large and diverse populations of microorganisms in hydrocarbon‐rich substances and contaminated environments.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that the autoxidation as a part of the deterioration process can accelerate the biodegradation process by producing smaller and easier compounds to be biodegraded or inhibits it by producing antibacterial products (e.g. formic acid) (Al-Darbi et al 2005). Therefore it can be concluded that the oxidation products could have affected the biodegradation tests in this study.…”
Section: Biodegradability Testsmentioning
confidence: 75%
“…The organic acids can also be formed as a result of microbial activity (Schricher et al 2009). It has also been suggested that the viscosity, structure and compostion of the oils and fats have an effect on the biodegradation rates and also oxidation products can either accelerate or inhibit the biodegradation (Al-Darbi et al 2005). Lapinskiené and Martinkus (2007) studied the intermediate biodegradation products of biodiesel, sunflower oil, diesel and beef grease.…”
Section: Biodegradability Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of oils biodegradation is influenced by several factors, such as nutrients, oxygen, pH, composition, concentration and bioavailability of the contaminants, chemical and physical characteristics and the pollution history of the contaminated environment [12]. Particularly, lack of essential nutrients such as nitrogen and phosphorus is one of the major factors affecting biodegradation of hydrocarbon by microorganisms in soil and water environment [13].…”
Section: Introductionmentioning
confidence: 99%